Statistical Evaluation of the Levels of Mercury Detected in Billfish in Costa Rica, for 2003-2013 - Rodríguez-Yáñez, Javier; Piedra-Marín, Gilberto (Uniciencia, 2016)
The billfish, like marlin, fish sailing and swordfish are pelagic predators, top in the food chain; large specimens contain significant levels of methyl mercury (MeHg+) in their tissues. In the current work, all mercury analysis records in billfish were reviewed, classified, tabulated, and statistically analyzed, for the period 2003-2013 by Laboratorio Nacional de Servicios Veterinarios or LANASEVE (National Laboratory of Veterinary Services). The mercury levels had a Poisson type distribution behavior; the majority of the analysis were associated with samples fluctuating in the range of fish 0.2 mg Hg/kg to 0.4 mg Hg/kg. Compared to swordfish, there was a greater dispersion in marlin mercury levels. Average mercury concentration in marlin was 0,583 mg Hg / kg, while in swordfish it was 0,533 mg Hg / kg. The Valores de Ingesta Semanal Tolerable Recomendada o ISTR (Tolerable Weekly Intake Values Recommended) for marlin consumption were 165 g/week for pregnant women and 96 g/week for children, meanwhile for swordfish were 180 g/week and 105 g/week, respectively. Slightly higher mercury levels in marlin suggest a lower weekly consumption compared to swordfish.